Theoretical Studies on Formation Mechanism of Levoglucosan in Pyrolysis of Cellobiose - Lan, Weijuan; Huang, Jinbao (Asian Journal of Chemistry, 2014)
The pyrolysis mechanism of cellobiose as a model compound was investigated using density functional theory methods at B3LYP/6-31++G(d,p) level. Three possible pyrolytic pathways were proposed and the standard thermodynamic and kinetic parameters in each reaction pathway were calculated at different temperatures. In pathway 1, two free radicals IM1 and IM2 are formed through homolytic cleavage of glycosidic bond and the homolysis reaction is endothermic with an energy of 316.65 kJ/mol. IM1 is further converted to levoglucosan P1 via transition state TS1 with an energy barrier of 211.51 kJ/mol. In pathway 2, levoglucosan P1 and glucopyranose P2 are formed through concerted reaction via transition state TS3 with an energy barrier of 270.09 kJ/mol. Compared to reaction pathway 1, the concerted reaction pathway 2 is kinetically favorable and levoglucosan is formed mainly through concerted reaction mechanism. In pathway 3, addition of H+ to cellobiose would enhance the breakage of glycosidic bond, but the intermediate IM3 formed can hardly be converted to levoglucosan.